The Development of a Popular Piano Textbook for Undergraduates - Wang, Lusi; Daoruang, Krisada (Journal of Cultural Analysis and Social Change, 2025)
This study investigated the teaching materials for popular piano for undergraduate students at regular universities. First, through a review of the literature, we found that there are few studies on popular piano teaching materials in China, and existing research is insufficiently in-depth. Academic research primarily focuses on classical piano and popular music, whereas research on popular piano mainly focuses on social research. The few popular piano teaching materials focus exclusively on amateurs. Then, through surveys and in-depth interviews with students, teachers and administrators in colleges and universities, we found that there are several key challenges and needs in popular piano teaching, including the lack of professional tutorials, insufficient support for improvisation, and the mismatch between existing resources and the specific needs of Chinese students. To address these problems, we developed a new textbook for undergraduate students of popular music, focusing on improving students' grasp of various styles, beginning with rhythm, harmony, and accompaniment, and gradually advancing their performance skills across these styles. Based on these surveys, the study recommends strengthening the curriculum, localizing instructional materials, enhancing teachers' professional development, and expanding performance opportunities for students. This study emphasizes the importance of combining technical ability with creative expression in popular music education to cultivate long-term musical creativity and performance skills.